Climate Change Attribution: When Is It Appropriate to Accept New Methods?. Issue 3 (30th March 2018) - Lloyd, Elisabeth A.; Oreskes, Naomi
Abstract: The most common approaches to detection and attribution (D&A) of extreme weather events using fraction of attributable risk or risk ratio answer a particular form of research question, namely "What is the probability of a certain class of weather events, given global climate change, relative to a world without?" In a set of recent papers, Trenberth et al. (2015, https://doi.org/10.1038/nclimate2657 ) and Shepherd (2016, https://doi.org/10.1007/s40641‐016‐0033‐y ) have argued that this is not always the best tool for analyzing causes, or for communicating with the public about climate events and extremes. Instead, they promote the idea of a "storyline" approach, which asks complementary questions, such as "How much did climate change affect the severity of a given storm?" From the vantage of history and philosophy of science, a proposal to introduce a new approach or to answer different research questions—especially those of public interest—does not appear particularly controversial. However, the proposal proved highly controversial, with the majority of D&A scientists reacting in a very negative and even personal manner. Some suggested the proposed alternatives amount to a weakening of standards, or an abandonment of scientific method. Here, we address the question: Why is this such a controversial proposition? We argue that there is no "right" or "wrong" approach to D&A in any absolute sense, but rather that in different contexts, society may have a greater or lesser concern with errors of a particular type. How we view the relative risk of overestimation versus underestimation of harm is context‐dependent. Plain Language Summary: Climate scientists sometimes analyze "extreme events, " like storms, floods, or droughts, and try to determine whether such extreme events were partially caused by climate change or not. The standard method for doing this analysis is called the "risk‐based" method. It carries the risk of underestimating the role of global climate change in extreme events and missing connections that are really there. A new, "storyline, " method has recently been proposed, meant to be applied when the conditions needed for the risk‐based method are lacking. The storyline method is like an autopsy: it gives an account of the causes of the extreme event—the flood or storm—and can indicate whether climate change was one of these causes. It carries the risk of false alarms, or of overstating the role of climate change. Proponents of each account are concerned about different risks. On our analysis, the two approaches are complementary, and the resistance to the storyline approach has arisen from undue conservatism and an under‐appreciation of how much scientific methods can and do change over time. We advocate more discussion of the societal risks of extreme events; the choice of method should depend on which risk is more worrisome in the case at hand. Key Points: A new, storyline, approach to analysis of extreme weather events has been offered, but encountered great resistance, which we explore Storyline methods may overstate anthropogenic contributions to extreme events, while risk‐based methods may understate them We believe scientists could achieve better balance in assessing these complementary risks, and choose appropriate methods accordingly